Island of the aunts - Ibbotson, Eva.; Hawkes, Kevin (New York : Scholastics, 2000)
As they get older, three sisters decide that they must kidnap children and bring them to their secluded island home to help with the work of caring for an assortment of unusual sea creatures.
Keywords: Animals, Mythical -- Fiction; Marine animals -- Fiction; Islands -- Fiction; Kidnapping -- Fiction; Aunts -- Fiction